17th International Working Conference on Requirements Engineering: Foundation for Software Quality (REFSQ 2011). Proceedings of the REFSQ 2011 Workshops REEW, EPICAL and RePriCo, the REFSQ 2011 Empirical Track (Empirical Live Experiment and Empirical Research Fair), and the REFSQ 2011 Doctoral Symposium - Brian Berenbach; Maya Daneva; Jörg Dörr; Samuel Fricker; Vincenzo Gervasi; Martin Glinz; Andrea Herrmann; Benedikt Krams; Nazim H. Madhavji; Barbara Paech; Sixten Schockert; Norbert Seyff (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2011)
This ICB Research Report constitutes the proceedings of the following events which were held during the Requirements Engineering: Foundation for Software Quality (REFSQ) conference 2011 in Essen, Germany. Requirements Engineering Efficiency Workshop (REEW). Requirements Prioritization for customer-oriented Software-Development (RePriCo). Workshop on Empirical Research in Requirements Engineering: Challenges and Solutions (EPICAL). Empirical Research Fair. Empirical Live Experiment. Doctoral Symposium
Keywords: 650; Softwareentwicklung; Qualitätsmanagement